The Effects of Shared School Technology Access on Students Digital Skills in Peru - German Bet; Julian Cristia; Pablo Ibarraran (Inter-American Development Bank (IDB), 2014)
This paper analyzes the effects of increased shared computer access in secondary schools in Peru. Administrative data are used to identify, through propensity-score matching, two groups of schools with similar observable educational inputs but different intensity in computer access. Extensive primary data collected from the 202 matched schools are used to determine whether increased shared computer access at schools affects digital skills and academic achievement. Results suggest that small increases in shared computer access, one more computer per 40 students, can produce large increases in digital skills (0. 3 standard deviations). No effects are found on test scores in Math and Language.
Keywords: I21; I28; 330